Anti-adhesion Property of the Potential Probiotic Strain Lactobacillus fermentum 8711 Against Methicillin-Resistant Staphylococcus aureus (MRSA) - Jayashree, Sathyanarayanan; Karthikeyan, Raman; Nithyalakshmi, Sampath; Ranjani, Jothi; Gunasekaran, Paramasamy; Rajendhran, Jeyaprakash (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is a multidrug-resistant pathogen and one of the leading causes of nosocomial infection worldwide. Probiotic bacteria play a significant role in preventive or therapeutic interventions of gastrointestinal infections in human as well as animals. In this study, we have investigated the adhesion property of the probiotic strain Lactobacillus fermentum MTCC 8711 and its ability to prevent the adhesion of MRSA to human colon adenocarcinoma cells, Caco-2. We have shown that L. fermentum could efficiently adhere to the Caco-2 cells. Also, we have shown that L. fermentum significantly reduced MRSA adhesion to Caco-2 cells. Three types of experiments were performed to assess the anti-adhesion property of L. fermentum against MRSA. Inhibition (Caco-2 cells were pre-treated with L. fermentum, and subsequently MRSA was added), competition (both L. fermentum and MRSA were added to Caco-2 cells simultaneously), and displacement or exclusion (Caco-2 cells were pre-treated with MRSA, and subsequently L. fermentum was added). In all three experiments, adhesion of MRSA was significantly reduced. Interestingly, L. fermentum could efficiently displace the adhered MRSA, and hence this probiotic can be used for therapeutic applications also. In cytotoxicity assay, we found that L. fermentum per se was not cytotoxic, and also significantly reduced the MRSA-induced cytotoxicity. The protective effect occurred without affecting Caco-2 cell morphology and viability.